An Empirical Study on Listed Company’s Value of Cash Holdings: An Information Asymmetry Perspective - Chuangxia Huang; Xin Ma; Qiujun Lan (Discrete Dynamics in Nature and Society)
The value of a company’s cash holdings is currently a hot issue in corporate finance research. Current studies have not reached a unified conclusion. Moreover, no one has ever studied that from the perspective of information asymmetry. However, there still exist disputes about the measurement of the degree of information asymmetry. Previous studies mostly adopt single index to analysis this issue, and the economic meaning it represents only reflects some information of asymmetric information, so it was one-sided and the conclusion also differ. Drawing on the market microstructure and the index of information asymmetry of managers and investors, this paper constructs a new proxy for information asymmetry based on the principal component analysis. We find that a company’s value of cash holdings decreases increasingly with its level of information asymmetry, and the relationship between information asymmetry and the value of cash holdings is nonlinear.